ICT SELF EFFICACY DAN CREATIVITY SEBAGAI DETERMINASI TECHNOPRENEURSHIP INTENTION - Riki Yakub Pirdaus; Kusnendi Kusnendi (FKIP Unswagati, 2022)
AbstractThis research aims to determine how the influence of ICT self-efficacy, and also creativity on technopreneurship intention. This research uses the explanatory survey method. The population in this study were students of Economic Education, Faculty of Teacher Training and Education, Siliwangi University class of 2017 to 2020, amounting to 452 people. The sample of this study amounted to 212 students. Based on the results of data processing, it showed that the ICT self-efficacy, creativity, and technopreneurship intention of Economic Education students are in the high category. In addition, the results of data analysis using SPSS 25 found that ICT self-efficacy and creativity had a positive and significant effect on technopreneurship intention with an influence magnitude of 47.7% and 52.3% were able to be influenced by other factors not included in this study.Keywords: ICT self efficacy, creativiy, tecnopreneurship intention